A Bridging Platform for Students and their Alumni using a Social Media Platform - Patil, Leena; Vaibhaw, Aayush; Tripathi, Shaurya; Ambade, Ananya; Sonekar, Mansi; Rajak, Vaishali (International Journal of Computer Sciences and Engineering, 2025)
Alumni Interconnect is a dynamic social networking platform designed to connect students, alumni, and faculty, fostering mentorship, career guidance, and professional networking. It bridges the gap between students and successful alumni, enabling knowledge-sharing and industry insights. The platform offers an intuitive user experience with features like profile management, an interactive feed, messaging, and video meetings for seamless engagement. A robust authentication system ensures security by preventing fake accounts, while admins regulate content to maintain professionalism. By integrating these features, Alumni Interconnect enhances alumni-student engagement, promoting career growth, mentorship, and a strong institutional community. Its focus on authenticity, security, and interactive learning makes it a premier hub for academic and professional development.